Agronomic and productive performance of new drought tolerant Cenchrus purpureus cultivars - Ledea Rodríguez, José Leonardo; Ray Ramírez, Jorge Valentín; Arias Pérez, Ramón Crucito; Cruz Tejeda, José Marcelino; Rosell Alonso, Guiselle; Reyes Pérez, Juan José (Agronomía Mesoamericana, 2018)
The productivity of pastures and forage is increasingly limited due to climate variability and prolonged drought periods. For that reason, it is necessary to cultivate plants that are tolerant and productive under conditions of seasonal drought. The objective of this work was to characterize the agronomic and productive performance of new drought tolerantCenchrus purpureus cultivars. Three cultivars (CT-601, CT-603, and CT-605) were used at different regrowth ages (60, 80, 100, and 120 days) in two climatic periods: rainfall and low rainfall from 2013 to 2014 in a representative ecosystem of Cauto Valley, Cuba. The cultivars were grown on Vertisol and were fertilized with organic fertilizer at a rate of 25 t/ha. Some agronomic variables and dry matter (DM) yield (t/ha) were evaluated under rainfed conditions. A randomized block design with factorial arrangement and its interaction (3x4x2) was used. DM yield was affected by the second order interaction, during the period of rainfall, CT-605 at the age of 120 days reached the best average (p≤0.001) and during the period of low rainfall, CT-603 and CT-605 were highlighted (p≤0.001). Weather-season interaction on cultivars had a significantly positive impact (p≤0.001) on the length of leaves of CT-601 in the period of rainfall. CT-605 increased (p≤0.001) the percentage of leaves and green stems in the period of rainfall, superscripts were equalized in the dry season. Cultivars showed an acceptable DM yield during the low rainfall period, morphological changes neither affected the development nor the productivity.